Perkembangan Indikator Ekonomi dan Kemakmuran Indonesia Dibandingkan dengan 6 Negara Tetangga Periode 2005-2012 - Lesmana, Theresia (Binus Business Review, 2014)
In this study, the writer attempts basically to look at the economic indicator from three things, there are output growth rate, unemployment rate and inflation rate. For state prosperity indicator, the writer uses Gross Domestic Product (GDP) per capita. Object of this study uses the data from seven countries. They are Indonesia, Malaysia, Thailand, Singapura, Filipina, India and Cina. Economic and state prosperity indicator is viewed from the growth of eight years period from 2005 until 2012. The writer uses secondary data that is available on websites, such as website of International Monetary Fund, Central Statistic Body and etc. The analysis shows that Indonesia is at fourth position for output growth rate, sixth position for unemployment rate, the second position for inflation rate and the highest position for GDP per capita.